Language commodity in the age of globalization - Badran, Loay (Kufa Journal of Arts, 2021)
This research deals with the most important manifestations of globalization that threaten the reality of the Arabic language, as it must be remedied before the danger escalates, which is still imminent in the Arabic language, which he considered to be the language of the Holy Qur’an. However, it is not possible to rely on that and abandon its responsibilities towards the protection of Arabic and thus its continuity and the continuity of its social, literary and religious civilization and its transition to the language of science, in which alone the nation’s hopes for progress, glory and continuity are fruitful, and in it alone the Arab unitary project based on the unity of this language and common history is crystallized.